The influence of the backing plate materials on microstructure and mechanical properties of friction spot extrusion brazing of AA2024-T3 aluminum alloy and Brass sheets. (February 2022) - Paidar, Moslem; Bokov, Dmitry; Mehrez, Sadok; Nasution, Mahyuddin K.M.; Ojo, Olatunji Oladimeji; Zain, Azlan Mohd
Abstract: In this study, the impact of the backing plate materials on microstructural and mechanical features during friction spot extrusion brazing of AA2024-T3 aluminum alloy and brass sheets by inserting Zn as an interlayer was investigated. Results indicated that the change of the backing plate material influentially affected the microstructure of the reaction layers at the interface of the AA2024/Zn/brass joint. Besides, it was found that the Zn interlayer could restrict the creation of deleterious intermetallic compounds at the interface. Moreover, the attained data revealed that the weld produced by the steel backing plate raised the fracture load of the joint in comparison to the other weld obtained by the copper backing plate by 35% even though the peak temperature was enhanced with a change in the backing plate material from copper to steel. The improvement in the tensile result of the steel backing plate-produced joint is owing to the good metallurgical bonding (complete filling of the pre-threaded hole) and presence of a larger amount of Al-Zn eutectic phase at the brazed zone. Graphical abstract: Unlabelled Image Highlights: A change of backing plate materials alters surface appearance (bottom side) and filling of pre-threaded hole in the joint. The use of Cu as backing plate produced a relatively weaker interfacial bonding and poor plastic deformation. The use of steel backing plate produced interfacial defect-free brazed zone.